First-principles calculations and thermodynamic assessment of the Nb–V system using CE-CVM - Kumar S.; Jindal V. (My University, 2025)
A thermodynamic assessment of the Nb–V system has been carried out based on first-principles calculations and all the available experimental thermodynamic and phase equilibria data. Mixed-parametric ab initio calculations were performed to calculate the enthalpy of mixing data with Special quasirandom structures (SQS) and cluster expansion (CE) method. The Gibbs energy of the bcc solid phase was described using tetrahedron approximation of the Cluster Expansion and Cluster Variation Methods (CE-CVM). A sub-regular solution model was used for describing Gibbs energy of the liquid phase. An optimal set of parameters has been obtained for describing the Gibbs energies of the liquid and solid phases in the Nb–V binary system. The calculated phase diagram and thermodynamic properties agree with experimental data. The relevance of CE-CVM has been demonstrated in the present case by calculating the solid phase's short-range order (sro) parameters as a function of composition and temperature. © 2022 Elsevier Ltd